2006
DOI: 10.1038/sj.onc.1210060
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of stage II colon cancer by non-neoplastic mucosa gene expression profiling

Abstract: We have assessed the possibility to build a prognosis predictor (PP), based on non-neoplastic mucosa microarray gene expression measures, for stage II colon cancer patients. Non-neoplastic colonic mucosa mRNA samples from 24 patients (10 with a metachronous metastasis, 14 with no recurrence) were profiled using the Affymetrix HGU133A GeneChip. Patients were repeatedly and randomly divided into 1000 training sets (TSs) of size 16 and validation sets (VS) of size 8. For each TS/VS split, a 70-gene PP, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
1
46
1
1
Order By: Relevance
“…Several studies have shown that the colorectal mucosa in patients with CRC is characterized by alterations at the DNA, RNA, and protein levels that can be associated with premalignant behavior (2)(3)(4)(5), metastatic potential (6), and prognosis (7)(8)(9). Dietary factors such as folate, alcohol, and methionine in combination with polymorphisms in genes like methylenetetrahydrofolate reductase may be associated with CRC because of their influence on DNA methylation processes (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the colorectal mucosa in patients with CRC is characterized by alterations at the DNA, RNA, and protein levels that can be associated with premalignant behavior (2)(3)(4)(5), metastatic potential (6), and prognosis (7)(8)(9). Dietary factors such as folate, alcohol, and methionine in combination with polymorphisms in genes like methylenetetrahydrofolate reductase may be associated with CRC because of their influence on DNA methylation processes (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Barrier et al (9) recently showed that microarray gene expression profiles of non-neoplastic mucosa could be used to predict the postoperative prognosis of stage II colon cancer patients. Previous studies at our laboratory have shown that the expression of folate-associated genes in mucosa is associated with the survival of CRC patients (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…The ovarian cancer dataset from Bild et al (5) were assayed with Affymetrix U133A (retrieved with record GSE3149 from Gene Expression Omnibus). Two colon cancer datasets were all generated with Affymetrix U133A arrays (7,6). The lung adenocarcinoma datasets from Shedden et al (8) were generated with Affymetrix U133A.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…If a gene has multiple probes, the average expression of multiple probes was used in the classification. The patient cohort from Barrier et al (6) was used as training set (n=50), while the cohort from another study by Barrier et al (7) was used as an independent validation set (n=24). A training model was built with the 25 signature genes to classify recurrence in colon cancer patients using a linear discriminant analysis function in SAS 9.1.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 1 more Smart Citation